CABI Publications 3 Governments, farmers and seeds in a changing Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Governments, farmers and seeds in a changing Africa by Elizabeth Cromwell 1996, 176pp price UKL30.00 ISBN 0 85198 9764